Implementasi Media Konstruktif Straw Connectors untuk Menstimulasi Motorik Halus dan Karakter Kolaboratif Siswa di TK Negeri Tamalate (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of fine motor skills and collaborative character is an essential foundation during the golden age period to support children’s academic readiness and social development. However, learning stimulation at Tamalate State Kindergarten is still largely dominated by conventional methods that lack variety and interactive activities. This community service program aims to implement constructive Straw Connectorsmedia as an innovative learning solution to stimulate children’s fine motor skills and cooperative character. The implementation methods included teacher workshops, classroom application with students through collaborative constructive play activities, and evaluation of learning achievements. The findings revealed a significant improvement in children’s fine motor skills, with the average score increasing from 1.67 in the Pre-Test to 3.27 in the Post-Test. Furthermore, 60% of the children achieved the Very Well Developed (BSB) category in collaborative character development. Through the use of Straw Connectorsmedia, students were able to create complex architectural products such as construction bridges and windmills. The study concludes that Straw Connectorsmedia is effective in improving visual-motor coordination, creativity, and collaborative skills while fostering social empathy through interdependent interaction among children during the learning process.